PARTISIPASI MASYARAKAT DAN PERBAIKAN AKSES MEMASUKI SEKOLAH LANJUTAN TINGKAT PERTAMA - Suyata Suyata (Jurnal Kependidikan, 1999)
Abstract This empirical study was carried out to answer feasibility questions for junior secondary education (JSE) development project in term of community acceptance, support and participation. There was belief, held widely, that the willingness and the ability of the community to assume their part, generate and mobilize their resources would guarantee good result. Accordingly, the dynamic interactions between supply and demand within the education sector should be clarified prior to the beginning of the project. Improving JSE access means bringing JSE closer to the legitimate users by taking into account the best matching dynamic, interactive supply-demand within the socio-economic and cultural context.  The assessment questions should deal with both the micro (school) level and the macro (community) one. The methodology (procedure and rules) relied upon rapid assessment through intensive educational and social discourses with a wide range of educational stakeholders in the bureaucratic offices and the community members in the field. An inventory and the interview guide were developed supported by secondary data and school observation. The general conclusions (related to policies not strictly to research) included: (1) the general public and school community constituencies tended to assume that the key to improve the JSE access was the supply of schooling facilities, especially school building.